EFFECT OF SYNCHROMATE-B SYSTEM AND HUMAN CHORIONIC GONADOTROPHIN(hCG) ADMINISTRATION ON FERTILITY RATE IN REPEAT BREEDER COWS - Selvaraju, M; Veerapandian, C; Kathiresan, D; Kulasekar, K; Chandrahasan, C (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The study was conducted in repeat breeder crossbred cows by control of oestrus using synchromate-B treatment alone or in combination with hCG supplementation at the time of AI. A total of 48 repeat breeder cows were divided into 3 groups. Cows in group I and II were treated with norgestomet ear implants for 9 days. At the time of implant insertion, 2ml of SMB injection was administrated to all these cows. Cows in group III served as control without any treatment. AI was done at 48 (first AI) and 72 (second AI) hours of implant removal in group I and II. Group III cows were artificially inseminated twice at 24 hours interval during natural oestrus. Group II cows were injected with 1500 IU hCG at the time of first AI. There was 100 per cent oestrus response in synchromate-B treated cows. The first service conception rate obtained was 43.75, 56.25 and 18.75 per cent, in group I, II and III, respectively.